CHARACTER ASSOCIATION OF SOYBEAN (Glycine max) LINES FOR YIELD CONTRIBUTING TRAITS (Bangladesh Journal of Plant Breeding and Genetics, 2015)
The present study was conducted with ten soybean genotype on correlation, path coefficient and genetic component of some important traits. Ten characters were studied to find out the suitable traits for the improvement of soybean yield. It was observed that yield per plot was positively correlated with pods per plant, seeds per pod, branches per plant, harvest index, days to maturity and plant height which revealed that selection based on these traits could significantly improved the grain yield of soybean. From the path coefficient analysis, it was observed that among the different yield contributing characters pods per plant, seeds per pod, plant height, 100 seed weight contributed maximum direct positive effect to yield per plot. Negative direct effect was observed for days to flowering and days to maturity, but its correlation with yield was positive. It was due to its positive indirect effect. The residual effect was found 0.175 which indicated that 82.50% of the variability was accounted for 10 yield and yield contributing traits included in the present study. Rest 17.50% variability might be controlled by other yield contributed traits that was not included in the present investigation.